High-entropy platinum alloy catalyst doped with non-metallic elements at interstitial sites, and preparation method and application thereof

CN116666672BActive Publication Date: 2026-10-30TONGJI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310695186.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-13
Publication Date
2026-10-30
Estimated Expiration
2043-06-13

AI Technical Summary

Technical Problem

然而熵稳定效应难以完全抵挡化学浸出和电化学氧化还原,在电化学反应中高熵催化剂仍然存在明显的表面重构和转化,导致性能的下降,因此需要进一步提高高熵合金的电化学稳定性

Benefits of technology

[0029]根据本发明所涉及的一种间隙位非金属元素掺杂的高熵铂合金催化剂的制备方法,通过将非金属元素掺杂到高熵纳米合金晶格间隙位,制备得到活性和稳定性同时大幅度提升的高熵纳米铂合金催化剂,且纳米合金的粒径尺寸理想,并在含有金属单原子位点的碳载体上分散均匀。本发明通过多种过渡金属元素的掺杂即高熵合金化的过程不仅实现了降低铂载量的目的,而且实现了对铂合金催化剂的电子和几何结构的连续调控;金属间隙间的非金属元素掺杂进一步强化铂原子晶格能,同时增加晶格之间的扩散能垒,因而在提高催化剂的活性同时又能增加其稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116666672B_ABST
    Figure CN116666672B_ABST
Patent Text Reader

Abstract

The application provides a preparation method of a high-entropy platinum alloy catalyst doped with a nonmetallic element at a lattice site, and comprises the following steps: S1, mixing a platinum salt, a transition metal salt, a nonmetallic source, a carbon carrier and a solvent to obtain a mixture; S2, subjecting the mixture to a reaction through microwave heating, and after the reaction, centrifuging, washing and vacuum drying to obtain a catalyst precursor; and S3, annealing and post-treating the catalyst precursor to obtain the high-entropy platinum alloy catalyst doped with the nonmetallic element at the lattice site. The catalyst comprises a carbon carrier containing a metal single-atom site and high-entropy platinum alloy particles doped with a nonmetallic element at a lattice site supported on the carbon carrier, the high-entropy platinum alloy particles are composed of Pt, three or more transition metal elements and one nonmetallic element doped at a lattice site of a platinum alloy, and have a face-centered cubic structure. The catalyst has outstanding activity and stability, and can greatly improve the performance of a fuel cell when applied to the fuel cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of fuel cell catalyst technology, specifically relating to a high-efficiency catalyst in which non-metallic elements are doped into the interstitial sites of a high-entropy platinum alloy lattice, as well as its preparation method and application. Background Technology

[0002] In proton exchange membrane fuel cells (PEMFCs), the overpotential of the cathode oxygen reduction reaction (ORR) is relatively large, requiring the use of highly active and stable catalysts. Currently, carbon-supported platinum (Pt) nanocatalysts are the most commonly used and effective catalysts for ORR, but their high price and stack loading (35g / 100kW) are significant obstacles to the further promotion of PEMFCs. To meet the performance targets for fuel cells in 2030 (platinum loading of 5g / 100kW, 9kW / L), catalysts that simultaneously meet the requirements of both activity and stability are still extremely rare. Therefore, there is an urgent need to design a catalyst that significantly improves both activity and stability.

[0003] It has been proven that alloying Pt with 3d transition metals is an effective method to improve catalyst activity and thus reduce the amount of Pt used. Among them, high-entropy alloy catalysts containing five or more elements have been found to have better performance than general alloys. On the one hand, the complex atomic configuration formed by random multi-element mixing can provide a variety of adsorption sites and a near-continuous binding energy distribution pattern, which may break the limitations of the traditional volcano curve relationship; on the other hand, due to the size differences between different elements and the resulting lattice distortion, the dissolution of transition metals can be effectively hindered, thereby improving stability. However, the entropy stabilization effect cannot completely resist chemical leaching and electrochemical redox reactions. In electrochemical reactions, high-entropy catalysts still have significant surface reconstruction and transformation, leading to a decline in performance. Therefore, it is necessary to further improve the electrochemical stability of high-entropy alloys. Summary of the Invention

[0004] This invention targets the performance goals of fuel cells in 2030 (platinum loading of 5g / 100kW, 9kW / L), focusing on strategies to simultaneously and significantly improve catalyst activity and stability. It provides a high-performance catalyst with non-metallic elements doped into the interstitial sites of a high-entropy platinum alloy lattice, along with its preparation method and applications. Based on a high-entropy alloy, this invention introduces additional lightweight non-metallic elements into the interstitial sites of the platinum alloy lattice. Through the metal-non-metal dp electron orbital coupling effect and the strain effect of the interstitial non-metallic atoms, the activity and stability of the catalyst are further enhanced. Furthermore, the preparation method of the high-entropy platinum alloy catalyst with interstitial non-metallic elements provided by this invention is simple, scalable, and yields catalysts with good consistency, exhibiting significant advantages over existing platinum-based catalysts.

[0005] This invention provides a method for preparing a high-entropy platinum alloy catalyst doped with interstitial nonmetallic elements, characterized by the following steps:

[0006] Step S1: The platinum salt, transition metal salt, non-metal source, carbon support and solvent are mixed to obtain a mixture;

[0007] Step S2: The mixture is reacted by heating in an oil bath or by microwave heating. After the reaction is complete, it is centrifuged, washed, and vacuum dried to obtain the catalyst precursor.

[0008] Step S3 involves annealing and post-treatment of the catalyst precursor to obtain a high-entropy platinum alloy catalyst doped with interstitial non-metallic elements.

[0009] In step S1, during mixing, the platinum salt, transition metal salt, and non-metal source are first ultrasonically dissolved in a solvent, and then a carbon support is added and ultrasonically dispersed to obtain a mixture.

[0010] In step S1, the solvent is an amide solvent.

[0011] In step S2, when the mixture is heated by microwave, the reaction temperature is 120℃-200℃, and the reaction time is 0.5h-4h.

[0012] In step S3, the post-treatment includes pickling, washing, and vacuum drying.

[0013] The high-entropy platinum alloy catalyst doped with interstitial non-metallic elements comprises a carbon support containing metal single-atom sites and high-entropy platinum alloy particles doped with interstitial non-metallic elements supported on a carbon substrate.

[0014] High-entropy platinum alloy particles doped with interstitial non-metallic elements consist of Pt, three or more 3d transition metal elements, and one non-metallic element doped at the interstitial sites of the platinum alloy lattice. They have a face-centered cubic (fcc) structure and a particle size of 2-8 nm.

[0015] The method for preparing high-entropy platinum alloy catalysts doped with interstitial non-metallic elements provided by this invention may also have the following feature: in step S1, the platinum salt is any one of chloroplatinic acid hexahydrate, sodium chloroplatinate, potassium chloroplatinate, and platinum acetylacetonate.

[0016] The transition metal salt is any one or a combination of at least two of the chloride, chlorate, nitrate, acetylacetone salt, and acetate salts of transition metals. Preferably, the type of transition metal salt is selected from any three or more combinations of Cu, Ni, Co, Fe, Mn, Co, Cr, Al, and W.

[0017] The non-metallic source is any one of nitrogen source, fluorine source, or boron source; the carbon support is any one or a combination of at least two of carbon black, carbon nanotubes, graphene, and acetylene black; and the solvent is any one of formamide, N,N dimethylformamide, or N,N dimethylacetamide.

[0018] The method for preparing high-entropy platinum alloy catalysts doped with interstitial non-metallic elements provided by the present invention may also have the following characteristics: the nitrogen source includes any one or more combinations of pipemidic acid, 4-aminoantipyrine, 3-aminopyrazole, and uric acid; the fluorine source includes any one or more combinations of tetrafluoroterephthalonitrile, polyvinylidene fluoride, trifluoroacetonitrile, and ammonium fluoride; and the boron source includes any one or more combinations of diborane, boric acid, tetraboric acid, and metaboric acid.

[0019] The method for preparing high-entropy platinum alloy catalysts doped with interstitial non-metallic elements provided by the present invention may also have the following characteristics: in step S1, the molar ratio of platinum salt to transition metal salt is (1-2):1, and two or more transition metal salts are added in equal molar amounts.

[0020] The preparation method of the high-entropy platinum alloy catalyst doped with interstitial non-metallic elements provided by the present invention may also have the following characteristics: in step S2, when the mixture is heated by an oil bath for reaction, the reaction temperature is 160℃-230℃ and the reaction time is 8h-16h.

[0021] The preparation method of the high-entropy platinum alloy catalyst doped with interstitial non-metallic elements provided by the present invention may also have the following characteristics: during annealing in step S3, the catalyst is first kept at 400℃-600℃ for 2h-4h in a predetermined atmosphere, and then naturally cooled to room temperature. The predetermined atmosphere is a mixture of inert gas and reducing gas, with the volume ratio of reducing gas being 10%-20%. The inert gas is any one or a combination of at least two of nitrogen, argon, helium or krypton, and the reducing gas includes hydrogen.

[0022] The preparation method of the high-entropy platinum alloy catalyst doped with interstitial non-metallic elements provided by the present invention may also have the following characteristics: when acid washing is performed in step S3, the acid solution used is any one of perchloric acid, sulfuric acid and nitric acid, the acid washing temperature is 60℃-80℃, the acid washing time is 6h-12h, the molar concentration of the acid solution is 0.2mol / L-1.5mol / L, and the solvent used in washing in step S3 is deionized water.

[0023] The present invention also provides a high-entropy platinum alloy catalyst doped with interstitial non-metallic elements, characterized in that it is prepared by the above-mentioned method for preparing high-entropy platinum alloy catalyst doped with interstitial non-metallic elements.

[0024] The high-entropy platinum alloy catalyst doped with interstitial non-metallic elements provided by the present invention may also have the following characteristics: the metal loading in the high-entropy platinum alloy catalyst doped with interstitial non-metallic elements is 20%-40%, of which the Pt loading is 10%-20%.

[0025] The high-entropy platinum alloy catalyst doped with non-metallic elements at interstitial sites provided by this invention may also have the following characteristic: the non-metallic elements are located at tetrahedral / octahedral interstitial sites in the high-entropy alloy particle lattice.

[0026] The high-entropy platinum alloy catalyst doped with non-metallic elements at interstitial sites provided by this invention may also have the following characteristics: metal single atoms located on the carbon support, including Pt single atoms and transition metal single atoms.

[0027] The present invention also provides the application of the above-mentioned high-entropy platinum alloy catalyst doped with non-metallic elements at interstitial sites in fuel cells, including its application in the cathode of H2-Air fuel cells or H2-O2 fuel cells.

[0028] The role and effect of invention

[0029] According to the present invention, a method for preparing a high-entropy platinum alloy catalyst doped with interstitial non-metallic elements is used to prepare a high-entropy nano-platinum alloy catalyst with significantly improved activity and stability by doping non-metallic elements into the interstitial sites of a high-entropy nano-alloy lattice. The nano-alloy has an ideal particle size and is uniformly dispersed on a carbon support containing metal single-atom sites. This invention, through the doping of multiple transition metal elements—a process known as high-entropy alloying—not only achieves the goal of reducing platinum loading but also enables continuous control over the electronic and geometric structure of the platinum alloy catalyst. The doping of non-metallic elements between the metal interstitials further strengthens the lattice energy of platinum atoms and increases the diffusion barrier between lattices, thus improving both the activity and stability of the catalyst.

[0030] Furthermore, the mixing method of first mixing platinum salt, transition metal salt and non-metal source and then adding carbon support in this invention helps the coordination between non-metal source and metal ions, thereby enabling non-metal elements to uniformly enter the interstitial sites of the lattice during the alloy particle growth stage, ensuring that non-metal elements are uniformly dispersed throughout the high-entropy alloy particles; at the same time, the heating reaction of the mixture by microwave heating is more efficient and direct, with better reaction efficiency, which can further improve the electrochemical performance of the prepared catalyst.

[0031] Therefore, the interstitial non-metallic element-doped high-entropy platinum alloy particles and metal single-atom sites in the interstitial non-metallic element-doped high-entropy platinum alloy catalyst of the present invention contribute to both activity and stability, resulting in outstanding intrinsic activity and stability. Its superior performance in PEMFC full cells far surpasses that of other platinum-supported catalysts both domestically and internationally. Furthermore, the preparation method of the interstitial non-metallic element-doped high-entropy platinum alloy catalyst of the present invention can be extended to most transition metals in periods 4, 5, and 6, and both low-temperature oil bath heating and microwave solvothermal methods are suitable for industrial production. Attached Figure Description

[0032] Figure 1 These are STEM and mapping images of the high-entropy alloy particles in the interstitial non-metallic element-doped high-entropy platinum alloy catalyst PtCuNiCoN / C prepared in Example 1 of the present invention, as well as a STEM image of the carbon substrate.

[0033] Figure 2 The images show low-resolution TEM images and corresponding particle size distribution statistics of the interstitial non-metallic element-doped high-entropy platinum alloy catalyst PtCuNiCoN / C prepared in Example 1 of this invention before and after 30,000 potential cycles.

[0034] Figure 3 These are TEM and EDS images of the interstitial nonmetallic element-doped high-entropy platinum alloy catalyst PtCuNiCoF / C prepared in Example 2 of this invention.

[0035] Figure 4 The LSV curves of the high-entropy platinum alloy catalyst PtCuNiCoN / C with interstitial non-metallic elements doped in Example 1 of the present invention and the multi-component nano-platinum alloy catalyst N-doping PtCuNiCo / C with nitrogen doped on a carbon substrate but without nitrogen doping in the lattice in Comparative Example 1 are shown.

[0036] Figure 5 The LSV curves are those of the high-entropy platinum alloy catalyst PtCuNiCoN / C doped with interstitial non-metallic elements prepared in Example 1, the high-entropy platinum alloy catalyst PtCuNiCoF / C doped with interstitial non-metallic elements prepared in Example 2, the high-entropy platinum alloy catalyst PtCuNiCoB / C doped with interstitial non-metallic elements prepared in Example 3, the high-entropy nano-platinum alloy catalyst PtCuNiCo / C prepared in Comparative Example 2, and a commercial Pt / C catalyst.

[0037] Figure 6 This is the stability test curve of the high-entropy platinum alloy catalyst PtCuNiCoN / C doped with interstitial non-metallic elements in Embodiment 1 of the present invention.

[0038] Figure 7 The stability test curve of the undoped nitrogen high-entropy nano-platinum alloy catalyst PtCuNiCo / C in Comparative Example 2 of this invention is shown.

[0039] Figure 8 These are the stability test curves of the commercial Pt / C catalyst in the test examples of this invention;

[0040] Figure 9 The polarization and power density curves of the high-entropy platinum alloy catalyst PtCuNiCoN / C doped with interstitial non-metallic elements in Example 1 of the present invention and the commercial Pt / C catalyst in H2-Air fuel cells are shown.

[0041] Figure 10 The polarization and power density curves of the high-entropy platinum alloy catalyst PtCuNiCoN / C doped with interstitial non-metallic elements in Example 1 of this invention are shown. Detailed Implementation

[0042] To make the technical means, creative features, objectives and effects of this invention easier to understand, the following embodiments, in conjunction with the accompanying drawings, specifically illustrate the interstitial non-metallic element doped high-entropy platinum alloy catalyst, its preparation method and application.

[0043] <Example 1>

[0044] This embodiment describes a method for preparing a high-entropy platinum alloy catalyst doped with interstitial non-metallic elements, comprising the following steps:

[0045] Step S1 involves mixing platinum salt, transition metal salt, non-metal source, carbon support, and solvent to obtain a mixture. The specific process is as follows:

[0046] 10 mg of platinum acetylacetonate, 6.4 mg of nickel acetylacetonate, 8.9 mg of cobalt acetylacetonate, 6.2 mg of copper acetylacetonate, and 30 mg of pipemidic acid were dissolved in 5 mL of N-N dimethylformamide (DMF), and then 10 mg of carbon black was added and ultrasonically dispersed to obtain a mixture.

[0047] Step S2 involves reacting the mixture using an oil bath or microwave heating method. After the reaction is complete, the mixture is centrifuged, washed, and vacuum dried to obtain the catalyst precursor. The specific process is as follows:

[0048] The mixture was transferred to a microwave reactor and reacted at 120°C for 2 hours. After the reaction was complete, the mixture was centrifuged and washed 3-5 times with a mixture of deionized water, ethanol and acetone, and then vacuum dried overnight to obtain the catalyst precursor.

[0049] Step S3 involves annealing and post-treatment of the catalyst precursor to obtain a high-entropy platinum alloy catalyst doped with interstitial non-metallic elements. The specific process is as follows:

[0050] The catalyst precursor was annealed at 450 °C for 2 h in a 10% H2 / Ar mixed atmosphere, then acid-treated with 0.2 MH NO3 solution at 80 °C for 6 h, followed by centrifugal washing three times with deionized water and vacuum drying overnight to obtain the high-entropy platinum alloy catalyst PtCuNiCoN / C doped with interstitial non-metallic elements.

[0051] Annealing temperature and holding time affect the alloying degree and particle size of the catalyst. Higher annealing temperature and longer holding time improve the alloying degree, but also increase the particle size. Insufficient annealing temperature and holding time result in insufficient alloying and phase segregation. In this embodiment, the annealing temperature was controlled at 450℃ and the annealing time was 2h to prepare a high-entropy platinum alloy catalyst PtCuNiCoN / C with interstitial non-metallic element doping and ideal particle size with sufficient alloying degree.

[0052] The high-entropy platinum alloy catalyst PtCuNiCoN / C prepared in this embodiment is a high-entropy nano-platinum alloy catalyst enhanced by interstitial non-metallic element doping.

[0053] Figure 1 These are STEM and mapping images of the high-entropy alloy particles in the interstitial non-metallic element-doped high-entropy platinum alloy catalyst PtCuNiCoN / C prepared in Example 1 of the present invention, as well as a STEM image of the carbon substrate.

[0054] Figure 1 middle, Figure 1 (a) shows the STEM and mapping images of high-entropy alloy particles in the PtCuNiCoN / C catalyst. Figure 1 (b) is a STEM image of the carbon substrate in the PtCuNiCoN / C catalyst.

[0055] like Figure 1As shown, various metal elements (Pt, Cu, Ni, Co) and nitrogen are clearly distributed uniformly within the high-entropy particles, indicating the successful synthesis of the interstitial nitrogen-doped high-entropy platinum alloy PtCuNiCoN. The STEM image of the carbon substrate shows numerous bright and dark spots, indicating the presence of metal single-atom sites on the carbon substrate. The bright spots represent Pt atoms, while the darker spots represent transition metal atoms. Therefore, it is proven that the interstitial non-metallic element-doped high-entropy platinum alloy catalyst PtCuNiCoN / C prepared in Example 1 comprises a carbon support containing Pt and transition metal single-atom sites and interstitial nitrogen-doped high-entropy platinum alloy particles supported thereon. The interstitial nitrogen-doped high-entropy platinum alloy particles PtCuNiCoN have a face-centered cubic (fcc) structure.

[0056] Figure 2 The images show low-resolution TEM images and corresponding particle size distribution statistics of the interstitial non-metallic element-doped high-entropy platinum alloy catalyst PtCuNiCoN / C prepared in Example 1 of this invention before and after 30,000 potential cycles.

[0057] Figure 2 middle, Figure 2 (a) Low-resolution transmission electron microscopy image and particle size distribution statistics of PtCuNiCoN / C catalyst; Figure 2 (b) Low-resolution transmission electron microscopy image and particle size distribution statistics of PtCuNiCoN / C catalyst after 30,000 electrochemical potential cycles.

[0058] like Figure 2 As shown, this embodiment prepared a high-entropy platinum alloy catalyst PtCuNiCoN / C with ideal interstitial non-metallic element doping by a simple and mild low-temperature microwave solvent method. Figure 1 The high-entropy platinum nanoparticles were found to be very uniformly distributed on the carbon substrate. After activation and 30,000 potential cycles, the morphology and particle size of the high-entropy alloy nanoparticles remained almost unchanged, indicating that nitrogen doping in the high-entropy alloy particles enabled the catalyst to maintain high stability and greatly improved the catalyst's activity and stability.

[0059] Furthermore, the preparation method of the interstitial nonmetallic element-doped high-entropy platinum alloy catalyst of the present invention can be extended to most transition metals in periods 4, 5, and 6 by using different transition metal precursors, and can be used to synthesize interstitial nitrogen-doped binary, ternary, and quaternary alloy catalysts. Table 1 shows the onset potential and half-wave potential of the extended catalyst of the present invention during ORR. Compared with alloy catalysts containing only three or four elements, high-entropy alloy catalysts containing five or more elements have higher onset potentials and half-wave potentials. This demonstrates that high-entropy alloy catalysts containing five or more elements have better performance than general alloys.

[0060] Table 1. Wave potential and half-wave potential of the extended catalyst of the present invention.

[0061] PtCuN / C 1.054 0.944 PtNiN / C 1.070 0.958 PtCoN / C 1.047 0.938 PtFeN / C 1.056 0.948 PtCuNiN / C 1.085 0.965 PtCuCoN / C 1.060 0.946 PtCuFeN / C 1.074 0.956 PtCuCrN / C 1.050 0.958 PtCuMnN / C 1.080 0.947 PtNiCoN / C 1.094 0.976 PtNiFeN / C 1.051 0.948 PtCoFeN / C 1.046 0.929 PtCuNiCoN / C 1.150 1.010 PtCuCoFeN / C 1.060 0.984 PtCuNiFeN / C 1.080 0.994 PtNiCoFeN / C 1.080 0.970 PtNiCoCrN / C 1.091 0.976 PtNiCoMnN / C 1106 0.984 PtCuNiMnN / C 1.117 0.984 PtCuNiCrN / C 1.109 0.976 PtCuNiCoFeN / C 1.090 1.004 PtCuNiCoMnN / C 1.080 0.970 PtCuNiFeMnN / C 1.117 0.984 PtCuNiFeCrN / C 1.115 0.985 PtCuNiCoCrN / C 1.087 0.976 PtCuNiCoAlN / C 1.088 0.965 PtCuNiCoIrN / C 1.075 0.984 PtCuNiCoMoN / C 1.066 0.958 PtCuNiFeCrN / C 1.071 0.973 PtCuNiCoWN / C 1.085 0.999

[0062] <Example 2>

[0063] In this embodiment, the preparation method of the high-entropy platinum alloy catalyst doped with interstitial non-metallic elements is the same as that in Example 1. Except for replacing the non-metallic source in step S1 with tetrafluoroterephthalonitrile, the rest is the same as in Example 1. Finally, the high-entropy platinum alloy catalyst PtCuNiCoF / C doped with interstitial non-metallic elements is prepared.

[0064] The high-entropy platinum alloy catalyst PtCuNiCoF / C prepared in this embodiment is a high-entropy nano-platinum alloy catalyst enhanced by interstitial non-metallic element doping.

[0065] Figure 3 These are TEM and EDS images of the interstitial nonmetallic element-doped high-entropy platinum alloy catalyst PtCuNiCoF / C prepared in Example 2 of this invention.

[0066] like Figure 3 As shown, the interstitial non-metallic element-doped high-entropy platinum alloy prepared in this embodiment has a particle size of approximately 4.5 nm and is very uniformly distributed on the carbon substrate. Further DES characterization revealed that the interstitial non-metallic element-doped high-entropy platinum alloy contains five elements: Pt, Cu, Ni, Co, and F, indicating the successful synthesis of the interstitial non-metallic element-doped high-entropy platinum alloy catalyst PtCuNiCoF / C. Therefore, it is proven that the interstitial non-metallic element-doped high-entropy platinum alloy catalyst PtCuNiCoF / C prepared in Example 2 comprises a carbon support containing Pt and transition metal single-atom sites and interstitial fluorine-doped high-entropy platinum alloy particles supported thereon. The interstitial fluorine-doped high-entropy platinum alloy particles PtCuNiCoF have a face-centered cubic (fcc) structure.

[0067] <Example 3>

[0068] In this embodiment, the preparation method of the high-entropy platinum alloy catalyst doped with interstitial non-metallic elements is the same as that in Example 1. Except for replacing the non-metallic source in step S1 with diborane, the rest is the same as in Example 1. Finally, the high-entropy platinum alloy catalyst PtCuNiCoB / C doped with interstitial non-metallic elements is prepared.

[0069] The high-entropy platinum alloy catalyst PtCuNiCoB / C prepared in this embodiment is a high-entropy nano-platinum alloy catalyst enhanced by interstitial non-metallic element doping.

[0070] Comparative Example 1

[0071] In this comparative example, based on the raw materials and preparation conditions of Example 1, an undoped nitrogen-based multi-component high-entropy nano-platinum alloy catalyst was first synthesized. Then, a non-metallic source was introduced to prepare a carbon-based nitrogen-doped multi-component high-entropy nano-platinum alloy catalyst, N-doping PtCuNiCo / C. The specific process is as follows:

[0072] In step S1, 10 mg of platinum acetylacetonate, 6.4 mg of nickel acetylacetonate, 8.9 mg of cobalt acetylacetonate, and 6.2 mg of copper acetylacetonate were dissolved in 5 mL of N-N dimethylformamide (DMF), and then 10 mg of carbon black was added and ultrasonically dispersed to obtain a mixture.

[0073] Step S2: Transfer the mixture to a microwave reaction vessel, react at 120°C for 1 hour, then add 30 mg of pipemidic acid, mix thoroughly, and continue reacting at 120°C for 1 hour. After the reaction is complete, centrifuge and wash the mixture 3-5 times with a mixture of deionized water, ethanol, and acetone, and then vacuum dry overnight to obtain the catalyst precursor.

[0074] Step S3: After annealing the catalyst precursor at 450°C for 2 hours in a 10% H2 / Ar mixed atmosphere, it was acid-treated with 0.2 MH NO3 solution and treated at 80°C for 6 hours. Subsequently, it was centrifuged and washed three times with deionized water and vacuum-dried overnight to obtain the carbon-based nitrogen-doped multi-component nano-platinum alloy catalyst N-dopingPtCuNiCo / C.

[0075] <Comparative Example 2>

[0076] In this comparative example, based on the raw materials and preparation conditions of Example 1, the non-metallic source used in Example 1 was removed, and an undoped nitrogen-based multi-component high-entropy nano-platinum alloy catalyst PtCuNiCo / C was prepared. The specific process is as follows:

[0077] In step S1, 10 mg of platinum acetylacetonate, 6.4 mg of nickel acetylacetonate, 8.9 mg of cobalt acetylacetonate, and 6.2 mg of copper acetylacetonate were dissolved in 5 mL of N-N dimethylformamide (DMF), and then 10 mg of carbon black was added and ultrasonically dispersed to obtain a mixture.

[0078] In step S2, the mixture is transferred to a microwave reactor, the reaction temperature is 120°C, the reaction time is 2 hours, and after the reaction is complete, it is centrifuged and washed 3-5 times with a mixture of deionized water, ethanol and acetone. Then it is vacuum dried overnight at a predetermined drying temperature of 60°C to obtain the catalyst precursor.

[0079] In step S3, the catalyst precursor was annealed at 450°C for 2 hours in a 10% H2 / Ar mixed atmosphere, then acid-treated with 0.2 MH NO3 solution, followed by centrifugation and washing three times with deionized water and vacuum drying overnight to obtain the high-entropy nano-platinum alloy catalyst PtCuNiCo / C.

[0080] <Test Example>

[0081] In this test example, a 60% commercial Pt / C catalyst produced by Johnson Matthey was compared with the interstitial non-metallic element-doped high-entropy platinum alloy catalyst PtCuNiCoN / C prepared in Example 1, the interstitial non-metallic element-doped high-entropy platinum alloy catalyst PtCuNiCoF / C prepared in Example 2, the interstitial non-metallic element-doped high-entropy platinum alloy catalyst PtCuNiCoB / C prepared in Example 3, the nitrogen-doped multi-component nano-platinum alloy catalyst N-doping PtCuNiCo / C prepared in Comparative Example 1, and the high-entropy nano-platinum alloy catalyst PtCuNiCo / C prepared in Comparative Example 2. The comparison tests included catalyst performance and stability tests, as detailed below:

[0082] I. Catalyst Performance Testing

[0083] Catalyst performance was tested using a rotating disk electrode (RDE) test. Figure 4 The LSV curves of the high-entropy platinum alloy catalyst PtCuNiCoN / C with interstitial non-metallic elements doped in Example 1 of the present invention and the nitrogen-doped carbon substrate multi-component nano-platinum alloy catalyst N-doping PtCuNiCo / C with nitrogen doped in the lattice in Comparative Example 1 are shown.

[0084] like Figure 4As shown, compared with the nitrogen-doped multi-component nano-platinum alloy catalyst N-dopingPtCuNiCo / C prepared by introducing a nitrogen source later in Comparative Example 1, the high-entropy platinum alloy catalyst PtCuNiCoN / C prepared by introducing a nitrogen source first in Example 1, which is doped with interstitial non-metallic elements, exhibits a significantly increased ORR activity. Therefore, compared with the method of first preparing alloy particles and then doping with non-metallic elements, the high-entropy platinum alloy catalyst prepared by introducing a non-metallic source first and then doping with non-metallic elements in situ in the preparation method of the present invention has better performance. By adding a non-metallic source when mixing various precursors, on the one hand, non-metallic elements can enter the interior of the high-entropy alloy, while non-metallic elements introduced by the subsequent synthesis method (introducing non-metallic elements after the catalyst particles are formed) mostly exist only on the surface; on the other hand, metal ions are anchored to the carbon support through coordination, thereby forming metal single-atom sites. Thus, the activity and stability of the high-entropy platinum alloy catalyst with interstitial doped non-metallic elements obtained by the preparation method of the present invention are greatly increased.

[0085] Figure 5 The LSV curves of the high-entropy platinum alloy catalyst PtCuNiCoN / C doped with interstitial non-metallic elements prepared in Example 1, the high-entropy platinum alloy catalyst PtCuNiCoF / C doped with interstitial non-metallic elements prepared in Example 2, the high-entropy platinum alloy catalyst PtCuNiCoB / C doped with interstitial non-metallic elements prepared in Example 3, the high-entropy nano-platinum alloy catalyst PtCuNiCo / C prepared in Comparative Example 2, and the commercial Pt / C catalyst are shown in Table 1.

[0086] Table 1. Experimental results related to LSV curves of PtCuNiCoN / C, PtCuNiCo / C, and commercial Pt / C catalysts.

[0087]

[0088] like Figure 5 As shown in Table 1, the high-entropy platinum alloy catalyst PtCuNiCoN / C with interstitial nonmetallic element doping in Example 1 has a mass activity (MA) of 7.79 A / mg at 0.9 V vs. RHE. Pt The intrinsic activity (SA) is 12.1 mA / cm. 2 The calculated electrochemical specific surface area (ECSA) is 64.4 m². 2 / g Pt ,

[0089] The high-entropy platinum alloy catalyst PtCuNiCoF / C doped with interstitial nonmetallic elements prepared in Example 2 exhibited a mass activity (MA) of 5.23 A / mg at 0.9 V vs. RHE. Pt ,

[0090] The high-entropy platinum catalyst PtCuNiCoB / C doped with interstitial nonmetallic elements prepared in Example 3 showed a mass activity (MA) of 3.95 A / mg at 0.9 V vs. RHE. Pt ,

[0091] In Comparative Example 2, the undoped nitrogen-rich high-entropy nanoplatinum alloy catalyst PtCuNiCo / C exhibited a maximum molecular weight (MA) of 3 A / mg at 0.9 V vs. RHE. Pt SA is 4.27 mA / cm 2 The calculated ECSA value is 70.3m. 2 / g Pt ,

[0092] The MA of the 60% commercial Pt / C catalyst in the test example was 0.1 A / mg. Pt SA is 0.18 mA / cm 2 The calculated ECSA value is 56.1m. 2 / g Pt .

[0093] The comparison shows that the mass activity (MA) and intrinsic activity (SA) of the high-entropy platinum alloy catalyst PtCuNiCoN / C with interstitial non-metallic elements doped in Example 1 are 78 and 67 times that of commercial Pt / C catalysts, respectively; while the MA and SA of the undoped high-entropy nano-platinum alloy catalyst PtCuNiCo / C in Comparative Example 2 are 28 and 24 times that of commercial Pt / C catalysts, respectively. The catalysts prepared in Example 1 and Comparative Example 2 have much higher activity than commercial Pt / C catalysts on the market.

[0094] Further comparison reveals that the MA and SA of the interstitial nonmetallic element-doped high-entropy platinum alloy catalyst PtCuNiCoN / C in Example 1 are 2.6 and 2.8 times that of the nitrogen-undoped high-entropy nano-platinum alloy catalyst PtCuNiCo / C in Comparative Example 2, respectively. This indicates that the anchoring and synergistic effects produced by the doping of interstitial nonmetallic elements significantly improve the activity and stability of the catalyst.

[0095] II. Stability Testing

[0096] Figure 6 This is the stability test curve of the high-entropy platinum alloy catalyst PtCuNiCoN / C doped with interstitial non-metallic elements in Example 1 of the present invention.

[0097] like Figure 6 As shown, after 30,000 potential cycles, the MA of the high-entropy platinum alloy catalyst PtCuNiCoN / C with interstitial non-metallic elements doped in Example 1 decreased by 20.8% and SA decreased by 17.4%, and its stability is at an advanced level in the reported literature and patents.

[0098] Figure 7 The figure shows the stability test curve of the undoped nitrogen high-entropy nano-platinum alloy catalyst PtCuNiCo / C in Comparative Example 2 of this invention.

[0099] like Figure 7 As shown, after 30,000 potential cycles, the MA of the undoped nitrogen high-entropy nano-platinum alloy catalyst PtCuNiCo / C in Comparative Example 2 decreased by 62.2% and SA decreased by 66.4%, and its stability was much lower than that of the interstitial non-metallic element doped high-entropy platinum alloy catalyst PtCuNiCoN / C in Example 1.

[0100] Figure 8 This is the stability test curve of the commercial Pt / C catalyst in the test examples of this invention.

[0101] like Figure 8 As shown, after 30,000 potential cycles, the MA of the commercial Pt / C catalyst used in the test example decreased by 82% and SA decreased by 79.4%. Its stability was lower than that of the undoped nitrogen high-entropy nano-platinum alloy catalyst PtCuNiCo / C in Comparative Example 2, and much lower than that of the interstitial non-metallic element doped high-entropy platinum alloy catalyst PtCuNiCoN / C in Example 1.

[0102] In this test example, the high-entropy platinum alloy catalyst PtCuNiCoN / C with interstitial non-metallic elements doped in Example 1 was also applied to the cathodes of H2-Air fuel cells and H2-O2 fuel cells, and its performance was compared with that of H2-Air fuel cells and H2-O2 fuel cells using commercial Pt / C catalysts.

[0103] Figure 9 The figures show the polarization and power density curves of the high-entropy platinum alloy catalyst PtCuNiCoN / C with interstitial non-metallic elements doped in Example 1 of this invention and the commercial Pt / C catalyst in an H2-Air fuel cell.

[0104] like Figure 9 As shown, compared to the H2-air fuel cell with a commercial Pt / C catalyst, the cathode Pt loading of the fuel cell with the interstitial non-metallic element-doped high-entropy platinum alloy catalyst PtCuNiCoN / C in Example 1 is reduced by ten times (0.15 mg). Pt / cm 2 Reduce to 0.015mgPt / cm 2 The total load decreased from 0.2 to 0.03 mg. Pt / cm 2 The peak power density in the fuel cell actually increased by 1.22 times (0.85 W / cm²). 2 Increased to 1.04 W / cm 2 The power mass activity increased even more, from 4.25 kW / g. Pt Increased to a record 34.7 kW / g Pt This demonstrates that the PtCuNiCoN / C catalyst prepared in Example 1 exhibits significantly higher activity than commercial Pt / C catalysts, indicating a high potential for commercial application.

[0105] Figure 10 The polarization and power density curves of the high-entropy platinum alloy catalyst PtCuNiCoN / C doped with interstitial non-metallic elements in Example 1 of this invention are shown.

[0106] Figure 10 The power density curve of the PtCuNiCoN / C H2-O2 fuel cell shows that the optimal power density obtained is 2.01 W / cm³. -2 Furthermore, at a voltage of 0.9V, based on the current corresponding to the polarization curve and the platinum loading of the cathode (0.015mg)... Pt / cm 2 The calculated mass activity was 3.14 A / mg. Pt This is higher than all previously reported work.

[0107] In summary, the high-entropy nano-platinum alloy catalyst with interstitial nitrogen doping enhanced in this invention exhibits outstanding intrinsic and mass activities that can be well expressed at the membrane electrode level. (Using 0.015 mg...) Pt cm -2 When the catalyst of this invention is applied to the cathode of an H2-Air fuel cell, the peak power density can reach 1.04 W / cm². -2 The power-mass activity reached a record high of 34.7 kW / gPt (total platinum loading of 0.03 mg). Pt cm -2 Its superior performance in H2-Air fuel cells (PEMFCs) far surpasses that of other catalysts reported to date. Furthermore, with the same platinum loading (0.015 mg... Pt cm -2 When the catalyst of the present invention was applied to the cathode of an H2-O2 fuel cell, the mass activity of the catalyst was 3.14 A / mg at 0.9V. Pt .

[0108] Therefore, the high-entropy nano-platinum alloy catalyst with interstitial nitrogen doping enhanced by this invention not only exhibits high activity and stability, but also demonstrates performance at the single-section membrane electrode level that far exceeds all core performance indicators set by the U.S. Department of Energy (DOE) in 2020 (total platinum loading <0.125 mg). Pt cm -2 At 0.9V, the mass activity is >0.44A / mg. Pt ).

[0109] The role and effect of the embodiments

[0110] As demonstrated in Examples 1 to 3, the method for preparing a high-entropy platinum alloy catalyst doped with interstitial non-metallic elements according to the present invention can dope non-metallic elements into the interstitial sites of a high-entropy nano-alloy lattice, thereby preparing a high-entropy nano-platinum alloy catalyst with significantly improved activity and stability. Furthermore, the nano-alloy has an ideal particle size and is uniformly dispersed on a carbon support containing metal single-atom sites. In addition, the method for preparing the high-entropy platinum alloy catalyst doped with interstitial non-metallic elements according to the present invention can be extended to most transition metals in periods 4, 5, and 6, and the low-temperature liquid-phase / microwave solvothermal method is suitable for industrial production.

[0111] As demonstrated by the test examples, firstly, compared to post-synthesis methods (introducing non-metallic elements after catalyst particle formation), the interstitial non-metallic element-doped high-entropy platinum alloy catalyst prepared by in-situ doping using the method of the present invention first introduces a non-metallic source and exhibits better performance. Secondly, compared to undoped nitrogen-based high-entropy nano-platinum alloy catalysts and commercial Pt / C catalysts, the interstitial non-metallic element-doped high-entropy nano-platinum alloy catalyst prepared by the present invention possesses outstanding intrinsic activity and stability. Furthermore, when applied to fuel cells, the superior performance of PEMFC full cells far surpasses that of other platinum-supported catalysts both domestically and internationally.

[0112] Therefore, the preparation method of the high-entropy platinum alloy catalyst doped with interstitial non-metallic elements of the present invention not only achieves the purpose of reducing the platinum loading through the doping of multiple transition metal elements, i.e., high-entropy alloying, but also achieves continuous control over the electronic and geometric structure of the platinum alloy catalyst; furthermore, the doping of non-metallic elements at the metal interstitial sites further enhances the lattice energy of platinum atoms and increases the diffusion energy barrier between lattices, thus improving the activity and stability of the catalyst. As a result, the high-entropy platinum alloy catalyst doped with interstitial non-metallic elements prepared by the present invention can significantly improve the performance of fuel cells when applied to fuel cells.

[0113] The above embodiments are preferred embodiments of the present invention and are not intended to limit the scope of protection of the present invention.

Claims

1. A method for preparing a high-entropy platinum alloy catalyst doped with interstitial nonmetallic elements, characterized in that, Includes the following steps: Step S1: The platinum salt, transition metal salt, non-metal source, carbon support and solvent are mixed to obtain a mixture; Step S2: The mixture is heated by microwave to react. After the reaction is complete, it is centrifuged, washed and vacuum dried to obtain the catalyst precursor. Step S3 involves sequentially annealing and post-treating the catalyst precursor to obtain a high-entropy platinum alloy catalyst doped with interstitial non-metallic elements. In step S1, during mixing, the platinum salt, the transition metal salt, and the non-metal source are first ultrasonically dissolved in the solvent, and then the carbon support is added and ultrasonically dispersed to obtain the mixture. In step S1, the solvent is an amide solvent. In step S2, when the mixture is reacted by microwave heating, the reaction temperature is 120℃-200℃, and the reaction time is 0.5h-4h. In step S3, the post-processing includes pickling, washing, and vacuum drying. The interstitial non-metallic element-doped high-entropy platinum alloy catalyst comprises a carbon support containing metal single-atom sites and interstitial non-metallic element-doped high-entropy platinum alloy particles supported on a carbon substrate. The high-entropy platinum alloy particles doped with interstitial non-metallic elements consist of Pt, three or more transition metal elements, and one non-metallic element doped in the interstitial sites of the platinum alloy lattice, with a particle size of 2-8 nm.

2. The method for preparing a high-entropy platinum alloy catalyst doped with interstitial non-metallic elements according to claim 1, characterized in that: in, In step S1, the platinum salt is any one of chloroplatinic acid hexahydrate, sodium chloroplatinate, potassium chloroplatinate, and platinum acetylacetonate. The transition metal salt is any one or a combination of at least two of the following: chloride, chlorate, nitrate, acetylacetone, and acetate salts of transition metals. The non-metallic source can be any one of nitrogen, fluorine, or boron. The carbon support is any one or a combination of at least two of carbon black, carbon nanotubes, graphene, and acetylene black. The solvent is any one of formamide, N,N dimethylformamide, and N,N dimethylacetamide.

3. The method for preparing a high-entropy platinum alloy catalyst doped with interstitial non-metallic elements according to claim 2, characterized in that: in, The nitrogen source includes any one or a combination of two or more of pipemidic acid, 4-aminoantipyrine, 3-aminopyrazole, and uric acid. The fluorine source includes any one or a combination of two or more of tetrafluoroterephthalonitrile, polyvinylidene fluoride, trifluoroacetonitrile, and ammonium fluoride. The boron source includes any one or a combination of two or more of diborane, boric acid, tetraboric acid, and metaboric acid.

4. The method for preparing a high-entropy platinum alloy catalyst doped with interstitial non-metallic elements according to claim 1, characterized in that: in, In step S1, the molar ratio of the platinum salt to the transition metal salt is (1-2):1, and two or more of the transition metal salts are added in equimolar amounts.

5. The method for preparing a high-entropy platinum alloy catalyst doped with interstitial non-metallic elements according to claim 1, characterized in that: in, In step S3, during annealing, the temperature is first maintained at 400℃-600℃ for 2-4 hours under a predetermined atmosphere, and then naturally cooled to room temperature. The predetermined atmosphere is a mixture of inert gas and reducing gas, wherein the volume percentage of the reducing gas is 10%-20%, and the inert gas is any one or a combination of at least two of nitrogen, argon, helium or krypton, and the reducing gas includes hydrogen.

6. The method for preparing a high-entropy platinum alloy catalyst doped with interstitial non-metallic elements according to claim 1, characterized in that: in, In step S3, the acid solution used for pickling is any one of perchloric acid, sulfuric acid, and nitric acid. The pickling temperature is 60℃-80℃, and the pickling time is 6h-12h. The molar concentration of the acid solution is 0.2 mol / L to 1.5 mol / L.

7. A high-entropy platinum alloy catalyst doped with interstitial non-metallic elements, characterized in that, The high-entropy platinum alloy catalyst prepared using the method described in any one of claims 1 to 6, which involves doping with non-metallic elements at interstitial sites, was obtained.

8. The high-entropy platinum alloy catalyst doped with interstitial non-metallic elements according to claim 7, characterized in that: in, The high-entropy platinum alloy catalyst doped with non-metallic elements at interstitial sites has a metal loading of 20%-40%, of which the Pt loading is 10%-20%.

9. The application of a high-entropy platinum alloy catalyst doped with interstitial nonmetallic elements as described in any one of claims 7 to 8 in a fuel cell.

Citation Information

Patent Citations

  • Catalyst

    CN109314248A

  • High-entropy alloy ORR and OER catalytic material and preparation method thereof

    CN115395031A